Further Observations and Analysis of the Rapidly Pulsating Subdwarf B Star EC 20117-4014 - Lopes, I (2006)
We present the results of further observations and the subsequent analysis of the rapidly pulsating subdwarf B star EC 20117-4014. Despite our efforts, the only pulsations detected were those already reported by O'Donoghue et al., at 137.3, 142.1, and 157.4 s. We attempted a detailed asteroseismological analysis by thoroughly exploring the four-dimensional parameter space defining our equilibrium stellar structures [Teff, logg, M*, logq(H)] in search of models that could account precisely for the three observed periodicities. We were able to isolate just two potential families of optimal models, one of which is to be preferred on the basis of the period fit achieved and the surface gravity inferred. To proceed, we used external constraints on the effective temperature from published independent optical spectroscopy. Unfortunately, the contamination of the optical spectrum of EC 20117-4014 made it hard to quantify the uncertainties on the estimated spectroscopic temperature of ~34,800 K, and consequently, we adopted the conservative point of view that the true value would lie somewhere in the rather broad interval 32,800-36,800 K. Despite this limitation, leading to less accurate estimates of structural parameters than has been possible before for isolated pulsating EC 14026 stars, we still find that our asteroseismological exercise has been quite fruitful. Indeed, on the basis of our current models, we find that EC 20117-4014 would have a (logarithmic) surface gravity in the range 5.848-5.864 dex, a total mass in the range 0.50-0.59 Msolar, and a (logarithmic) fractional mass of its H envelope in the interval from -4.10 to -4.25 dex. From these primary parameters, we obtained useful estimates of secondary quantities such as the radius, the luminosity, the absolute visual magnitude, and the distance.